Reclaiming Catholicism: treasures old and new - Groome, Thomas H. (Orbis Books, 2010)
Preface / Thomas H. Groome -- Introduction / Michael J. Daley -- Part I: Perspectives -- Reclaiming our past and moving forward : a pervasive faith / James D. Davidson -- Becoming a theologian : ressourcement, personal, and ecclesial / Francine Cardman -- Studying the Bible, then and now / Dianne Bergant -- Jesus : a change in emphasis / Luke Timothy Johnson -- The church : Catholicism before and after Vatican II / Richard P. McBrien -- The mass : heaven on earth / John F. Baldovin -- The humbling of the priesthood / Donald Cozzens -- Catholics among southern neighbors in the 1950's / Jeffrey Gros -- Our ancestors would be incredulous : Vatican II and the religious other / Mary C. Boys -- The pre-Vatican II church and women : not just doubt / Susan A. Ross -- Sin : don't lose all that old time Catholic guilt / Charles E. Curran -- From the treasury of vowed women religious : the past remembered, the present embraced / Christine Vladimiroff -- The pre-Vatican II parish: heaven in a heartless world / James J. Bacik -- Catholic teaching on sexuality : from romanticism to reality / Christine E. Gudorf -- The afterlife : death, judgment, purgatory, heaven, hell / Zachary Hayes -- Part II: Personalities -- John Courtney Murray : theologian of religious freedom / David Hollenbach -- Leonard Feeney : in memoriam / Cardinal Avery Dulles -- Madeleva Wolff, C.S.C. : woman of faith and vision / Gail Porter Mandell -- Pierre Teilhard de Chardin : communion with God through the earth / John F. Haught -- Thomas Merton: monk and prophet for the world / Thomas P. Rausch -- Virgil Michel and Godfrey Diekmann : full, active, and conscious participation / Mary Collins -- Fulton J. Sheen: the man with hypnotic eyes / Mark Massa -- John Tracy Ellis: historian and priest / Thomas J. Shelley -- Father charles e. coughlin: ?the radio priest / Mary Christine Athans -- Msgr. George Higgins and Msgr. John Ryan : public intellectuals and social reformers / Kenneth R. Himes -- Mary Perkins Ryan : loyal and prophetic woman of the church / Padraic O'Hare -- Marie Augusta Neal, SND de Namur : passionate voice for justice / Mary E. Hines -- African American Catholics : witnesses to fidelity / Cyprian Davis -- Dorothy Day and Peter Maurin / Robert Ellsberg -- Mary Luke Robin, SL : about her father's/mother's business / Theresa Kane -- Theodore M. Hesburgh, C.S.C. : leadership spanning two centuries / Richard P. McBrien -- Part III: Practices -- Questions and answers again from the Baltimore catechism / Thomas H. Groome -- Catholic schools : daily faith / Karen M. Ristau -- Amica fidelis, ora pro nobis : devotion to Mary / Ada Maria Isasi-Diaz -- Contraception : conflict and estrangement in the recent Catholic past / Leslie Woodcock Tentler -- The last sacrament : from extreme unction to the anointing of the sick / William Madges -- All the angels and saints : what happened to them / Dolores R. Leckey -- Catholic Eucharist, before and after Vatican II / Richard Rohr -- First confession : Bless me Father, for I have sinned / Kate Dooley -- Asceticism : then and now / Wilkie Au -- The Rosary : a treasure to be rediscovered / Thomas H. Groome -- Catholics growing up : the legion of decency / Richard Blake -- The angelus : praying throughout the day / Bishop Robert F. Morneau -- The eucharistic fast : a long past into the present / Berard L. Marthaler -- Lent : no feasting without fasting / Ronald Rolheiser